Lignin - Trends and Applications 2018
DOI: 10.5772/intechopen.71208
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Variability of Lignin in Biomass

Abstract: The objective of this chapter is to provide a concise overview of lignin composition and structure in different species and materials (wood, barks and nonwood plants). It includes a brief review on the lignin precursors and their polymerization as well as of the analytical tools used for lignin characterization from wet chemical to spectroscopic methods. Wood of gymnosperms is characterized by high lignin content (25-35%) and a HG-type of lignin with more guaiacyl (G) units and a small portion of p-hydroxyphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
82
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 171 publications
10
82
1
5
Order By: Relevance
“…Softwood lignins are mainly composed of guaiacyl units, and thus are classified as G-type lignin. Hardwood lignins are mainly composed of different proportions of guaiacyl-syringil (GS-type) [ 24 , 25 ]. Grass lignins have a mixture of the three aromatic units (HGS), and contain a higher proportion of p -coumaryl alcohol (H)-derived units than other lignin types [ 26 , 27 ].…”
Section: Ligninmentioning
confidence: 99%
“…Softwood lignins are mainly composed of guaiacyl units, and thus are classified as G-type lignin. Hardwood lignins are mainly composed of different proportions of guaiacyl-syringil (GS-type) [ 24 , 25 ]. Grass lignins have a mixture of the three aromatic units (HGS), and contain a higher proportion of p -coumaryl alcohol (H)-derived units than other lignin types [ 26 , 27 ].…”
Section: Ligninmentioning
confidence: 99%
“…As a hardwood lignin, WL is a less condensed, S/G lignin (S/G=1.25,), expected to be closer in structure to the native lignin with more β‐O‐4 linkages, due to the relatively mild conditions (P factor ∼691) in processing. On the other hand, as a softwood G‐lignin, KL has been documented to have a highly modified condensed structure, with notably less β‐O‐4 linkages, and it is abundant in atypical structures, such as stilbenes and aryl enol ethers . Additionally, our results show that the free phenolic hydroxyl group content (PhOH) of KL is much higher (4.93 mmol g −1 ) as compared to WL (2.28 mmol g −1 ).…”
Section: Resultsmentioning
confidence: 57%
“…The monomer distribution showed that, as expected, the major monomers were guaiacyl monomers (81% and 88%, respectively) followed by syringyl monomers (10% and 5%, respectively). As a thumbnail rule, syringyl monomers are not present in pine lignins; however, it has been reported that small amounts can be found in pine barks [ 57 ]. 31 P NMR spectrum of derivatized SeolA confirmed the presence of syringyl units by the presence of a shoulder at 143.1 ppm.…”
Section: Resultsmentioning
confidence: 99%